Toxicity and cosmetic outcome after hypofractionated whole breast irradiation and boost-IOERT in early stage breast cancer (HIOB): First results of a prospective multicenter trial (NCT01343459). (May 2020) - Fastner, Gerd; Reitsamer, Roland; Urbański, Bartosz; Kopp, Peter; Murawa, Dawid; Adamczyk, Beata; Karzcewska, Aldona; Milecki, Piotr; Hager, Eva; Reiland, Juliann; Ciabattoni, Antonella; Matuschek, Christiane; et al.
Highlights: Overall treatment tolerance of HWBI plus IOERT as a boost is excellent. Acute and late toxicity are mild. Postoperative cosmetic appearance is not impaired. T-size, tube diameter, age and fibrosis are negative predictors for breast cosmesis. Abstract: Background and purpose: To assess the role of intraoperative radiation with electrons (IOERT) as tumor bed boost followed by hypofractionated whole breast irradiation (HWBI) after breast conserving surgery (BCS) of patients with low to intermediate risk breast cancer focusing on acute/late toxicity and cosmetic outcome. Material and methods: In 2011, a prospective multicenter trial (NCT01343459) was started. Treatment consisted of BCS, IOERT (11.1 Gy) and HWBI (40.5 Gy in 15 fractions). In a single-arm design, 5-year IBR-rates are benchmarked by a sequential ratio test (SQRT) against best published evidences in 3 age groups (35–40 y, 41–50 y, >50 y). Acute/late toxicity and cosmesis were evaluated by validated scorings systems. Results: Of 627 eligible patients, 44 were excluded, leaving 583 to analyze. After a median follow-up (FUP) of 45 months (range 0–74), for acute effects CTCAE-score 0/1 was noted in 91% (end of HWBI) and 92% (4 weeks later), respectively. Late toxicity Grading 0/1 (mean values, ranges) by LENT-SOMA criteria were observed in 92.7% (89–97.3) at 4/5 months, rising to 96.5% (91–100) at 6 years post HWBI. Baseline cosmesis after wound healing prior to HWBI was scored as excellent/good in 86% of cases by subjective (patient) and in 74% by objective (doctor) assessment with no impairment thereafter. Conclusions: Acute and late treatment tolerance of a combined Boost-IOERT/HWBI regimen is excellent in short/mid-term assessment. Postoperative cosmetic appearance is not impaired after 3 years FUP.